A ferret brain slice model of oxygen–glucose deprivation captures regional responses to perinatal injury and treatment associated with specific microglial phenotypes. Issue 2 (23rd November 2021) - Wood, Thomas R.; Hildahl, Kate; Helmbrecht, Hawley; Corry, Kylie A.; Moralejo, Daniel H.; Kolnik, Sarah E.; Prater, Katherine E.; Juul, Sandra E.; Nance, Elizabeth
Abstract: Organotypic brain slice models are an ideal technological platform to investigate therapeutic options for hypoxic‐ischemic (HI) brain injury, a leading cause of morbidity and mortality in neonates. The brain exhibits regional differences in the response to HI injury in vivo. This can be modeled using organotypic brain slices, which maintain three‐dimensional regional structures and reflect the regional differences in injury response. Here, we developed an organotypic whole hemisphere (OWH) slice culture model of HI injury using the gyrencephalic ferret brain at a developmental stage equivalent to a full‐term human infant in order to better probe region‐specific cellular responses to injury. Each slice encompassed the cortex, corpus callosum, subcortical white matter, hippocampus, basal ganglia, and thalamus. Regional responses to treatment with either erythropoietin (Epo) or the ketone body acetoacetate (AcAc) were highly heterogenous. While both treatments suppressed global injury responses and oxidative stress, significant neuroprotection was only seen in a subset of regions, with others displaying no response or potential exacerbation of injury. Similar regional heterogeneity was seen in the morphology and response of microglia to injury and treatment, which mirrored those seen after injury in vivo. Within each region, machine‐learning‐based classification of microglia morphological shifts in response to injury predicted the neuroprotective response to each therapy, with different morphologies associated with different treatment responses. This suggests that the ferret OWH slice culture model provides a platform for examining regional responses to injury in the gyrencephalic brain, as well as for screening combinations of therapeutics to provide global neuroprotection after injury.